Strategi Guru Pendidikan Agama Islam dalam Membentuk Nilai Moral di SMA PGII 2 Bandung - Alhinja Algifari Nugraha; Nazwa Nurazizah; Muhammad Iqbal Imanullah; Umar Rosadi (Jurnal Dirosah Islamiyah, 2025)
This study is motivated by the phenomenon that the formation of students' morals is a crucial aspect in Islamic education, especially in the midst of increasingly complex social challenges. Islamic Religious Education (PAI) teachers play a strategic role in internalizing moral values to students. This study aims to examine in depth the strategies of PAI teachers in shaping moral values at SMA PGII 2 Bandung, a secondary education institution known for its strong Islamic nuances. The research approach is qualitative and the method used is descriptive. Data collection techniques are through direct interviews with teachers, principals, and students, as well as literature studies from various previous scientific references. The results showed that PAI teachers play an active role in fostering student morals through a personal approach, direct supervision of the implementation of worship, and strengthening a religious school culture. The strategies used are tailored to the individual character of the students, in line with the school's vision and mission in forming a noble generation. This finding shows that the synergy between the role of teachers and the Islamic school environment is the key to building students' character comprehensively.